Perspektif Penonton 2Gether: The Movie Terhadap Hubungan Relasi Seksual Sejenis - Ashari, Erina Prasdila; Trinugraha, Yosafat Hermawan; Astutik, Dwi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
In recent years, the Thai entertainment industry has begun to increase the number of productions of male love TV drama series. Fans of boys love content are now spread in various countries in the world. The popularity of the boys love genre series has penetrated to various countries including Indonesia. This study contains the views or perspectives of viewers of boys love genre films on same-sex relationships. The method used in this study is qualitative with a reception analysis approach. Sampling using purposive sampling techniques with data collection techniques in the form of interviews conducted online with 7 informants. Stuart Hall's Reception Analysis Theory and Judith Butler's Queer Theory were chosen as audience Reception analysis knives. Based on the results of the study that informants do not mind every scene in the 2Gether movie. But there are some informants who consider homosexuality only in boys love shows, because homosexuals are different or contrary to the culture and religion in Indonesia.